Alasan Gugat Cerai Pada Perkawinan Di Bawah Umur Di Kabupaten Sleman - Herawati, Tri Ratna; Muthmainnah, Muthmainnah; Sembodo, Cipto; Sari, Ika Kartika; Fadli, Sahril (Universitas Cokroaminoto Yogyakarta, 2025)
Based on case data received at the Sleman Regency Religious Court in 2021–2022, there has been an increase in the number of divorce cases, with 76% of the total cases being divorce lawsuits filed by wives, while 24% were divorce lawsuits filed by husbands. This empirical legal research found that from the perspective of Islamic Law, divorce is permitted if household life can no longer be maintained. However, Islam still prioritizes mediation and peaceful resolution before a divorce decision is made. The Compilation of Islamic Law and the Marriage Law in Indonesia also regulates the age limit for marriage and the divorce lawsuit mechanism to protect the rights of married couples. This research is expected to provide insight to the public and policy makers regarding the impact of early marriage and the importance of mental and economic readiness before marriage. In addition, the results of this study can be a reference in formulating divorce prevention policies among young couples.